The effect of reverse intergenerational support on the happiness of Chinese older adults: A moderating effect analysis based on role conflict - Zhang, Hongfeng; Li, Shunyi; Dai, Wenwen; Wang, Hanning (Frontiers in Psychology, 2023)
Intergenerational support is bidirectional, and reverse intergenerational support refers to parents providing financial support, time support, and spiritual support to their offspring. The emergence of reverse intergenerational support has created role conflicts among different groups of older adults. Based on survey data from 3,170 elderly people in eight sample provinces in China, this paper empirically investigates the relationship between reverse intergenerational support and the happiness of the elderly in contemporary China and the moderating effect of role conflict in it, using an ordered logit model. It was found that, first, reverse economic support reduces the happiness of the elderly, and reverse time support and reverse spiritual support can significantly enhance the happiness of the elderly. Second, in the presence of role conflict, the effect of reverse time support and reverse spiritual support on the enhancement of older adults’ happiness was suppressed; in the presence of role enhancement, the effect of reverse economic support on the reduction of older adults’ happiness was mitigated. The above findings provide new empirical evidence for understanding the relationship between reverse intergenerational support and the happiness of the elderly, which is prevalent in contemporary China, and offer new insights for enhancing happiness.